Joko Widodo sebagai Faktor Penentu Pilpres 2024 dalam Kemenangan Paslon 02 Prabowo-Gibran - Burhan Hakim, Ahmad; Satryo Pringgo Sejati (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
Elections are one of the most important parts in the implementation of modern democracy, and Indonesia is no exception. So the election becomes a contestation of the ideas of each candidate pair to gain the sympathy of the people as voters. In this way, elections can become very sacred for the continuation and development of politics and democracy in a country in the future. The victory of candidate pair 02 Prabowo-Gibran certainly did not win in a vacuum. In fact, Joko Widodo's role is vital and has a strong influence as a determinant of the victory of candidate pair 02. In this way, the Indonesian people still seem to really like and may even still be satisfied with Jokowi's performance in the last five years of his leadership. The results of survey institutions show that the level of public satisfaction with Jokowi's performance while leading the government is quite high. So it could be that this number also represents the voters' rationality in choosing Prabowo-Gibran because Jokowi is also a supporter of the candidate pair. So Jokowi, with these data and figures, is still a strong magnet for voters to participate in making their choice. The methodology we use in this research is descriptive qualitative, using a library research approach to obtain the data and data sources we need. The findings that we got are that it is true that Jokowi was one of the determining factors in the victory of candidate pair 02 Prabowo-Gibran, besides the fact that Jokowi is Gibra's biological father.